Determining the Production Amount of Tofu Using Mamdani Method (Case Study: UD. Eko Jaya Pasuruan Tahu Factory) - Wahyu Santoso; Uce Indahyanti (Universitas Muhammadiyah Sidoarjo, 2022)
Lots of problems that contain uncertainty arise in this world. Fuzzy logic is one of the methods created to analyze systems that contain these uncertainties. In this study, the author uses the Mamdani method or often also known as the Min-Max method which is an application of the fuzzy method. The purpose of this study was to determine the amount of tofu production at UD. Eko Jaya Pasuruan by using the MinMax (Mamdani) method. The data used is the number of requests and the amount of product inventory at UD. Eko Jaya in June 2022. After that, data analysis was carried out using the Mamdani fuzzy method to determine the amount of production. The design of the system to obtain the output is carried out in several stages, including (a) forming fuzzy sets, (b) application of implication functions, (c) forming rules, and (d) affirmation (defuzzification). In this study, defuzzification was carried out using the centroid method. From the results of data processing that has been carried out, using input variables in June 2022, namely the number of requests of 14,000 pcs and the amount of inventory of 3000 kg each producing an output of 13,808 pcs.